2019
DOI: 10.3390/molecules24213949
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Anti-Tumor Herb Bred in a Tropical Fruit: Insight into the Chemical Components and Pharmacological Effects of Momordicae Semen

Abstract: Gac fruit (Momordica cochinchinensis Spreng) is a popular tropical fruit in southeast Asia. What is amazing is that its seeds (Momordicae Semen) and arils are traditional herbs with anti-tumor activity, and have protected human health for more than 1000 years. In recent years, its anti-tumor activity has received extensive attention and research. This manuscript summarized the chemical composition of saponins, fatty acids, volatile constituents, proteins, peptides, and other components from Momordicae Semen (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…Spreng., commonly known as Gac fruit, is a perennial dioecious cucurbit plant that originated in South and Southeast Asia and is widely sold for dietary and medicinal purposes. Reportedly, Momordica cochinchinensis can effectively inhibit the growth of cancer cells, such as gastric cancer, liver cancer, and esophageal cancer cells [ 39 ]. CMSP, as an important active component of Momordica cochinchinensis , has been reported to affect NF-κB signaling pathways [ 40 ], which are closely related to the expression of glutathione.…”
Section: Resultsmentioning
confidence: 99%
“…Spreng., commonly known as Gac fruit, is a perennial dioecious cucurbit plant that originated in South and Southeast Asia and is widely sold for dietary and medicinal purposes. Reportedly, Momordica cochinchinensis can effectively inhibit the growth of cancer cells, such as gastric cancer, liver cancer, and esophageal cancer cells [ 39 ]. CMSP, as an important active component of Momordica cochinchinensis , has been reported to affect NF-κB signaling pathways [ 40 ], which are closely related to the expression of glutathione.…”
Section: Resultsmentioning
confidence: 99%
“…Momordica cochinchinensis , also known as Gac or red melon, is a tropical plant native to South Asia and northern Australia [ 56 , 168 ]. Although, usually, aril (flesh surrounding the seeds) is the only consumed part of the fruit, in traditional Chinese medicine Gac seeds were considered to have therapeutic effects and were used to treat liver and spleen disorders, fluxes, swelling, bruises, hemorrhoids, or rheumatic pain [ 56 , 67 ].…”
Section: Chemical Content Of Seeds Eaten Separately and Biological Ac...mentioning
confidence: 99%
“…Several studies have demonstrated antiproliferative, antimigration, anti-invasion, and cytotoxic effect of M. cochinchinensis toward cancer cells [ 67 , 168 , 173 ]. Seed extract significantly inhibited the proliferation of ZR-75-30 human breast cancer cell line—50% growth inhibitory concentrations were 93.24, 34.04, and 53.43 μg/mL, at the incubation times of 24, 48, and 72 h, respectively.…”
Section: Chemical Content Of Seeds Eaten Separately and Biological Ac...mentioning
confidence: 99%
“… 76 In addition, Chinese herbal medicines and their active ingredients, such as Momordicae Semen ( Mubiezi ), curcumin (an active ingredient of Curcumae Longae Rhizoma) and Jia-Wei-Tong-You-Tang (Persicae Semen, Carthami Flos, Cimicifugae Rhizoma, Arecae Semen, Scutellariae Barbatae Herba, and Hedyotis Diffusa e Herba) can also inhibit cell proliferation to exert anti-EC effects. 77 - 79 The mechanism of action of TCM against EC is detailed in Figure 2 .…”
Section: Anti-ec Mechanisms Of Tcmmentioning
confidence: 99%